2004
DOI: 10.1002/hup.578
|View full text |Cite
|
Sign up to set email alerts
|

Ziprasidone‐related neuroleptic malignant syndrome in a patient with Parkinson's disease: a diagnostic challenge

Abstract: A case of neuroleptic malignant syndrome (NMS) in a patient with Parkinson's disease (PD) is presented. The syndrome was precipitated by the atypical antipsychotic, ziprasidone. The challenge of recognizing NMS in a patient with underlying parkinsonian symptoms, where prominent symptom overlap can occur, is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…A patient with resistant psychosis responded to the treatment with a maximum dose of 80 mg/d of ziprasidone without worsening of motor function (Connemann and Schondeldt-Lecuona, 2004). Another PD patient was treated with 40 mg of ziprasidone and developed elevation of creatinine kinase and body temperature so that neuroleptic malignant syndrome was discussed in this patient and ziprasidone was stopped (Gray, 2004). More data concerning the treatment of psychosis in PD with ziprasidone are lacking.…”
Section: Discussionmentioning
confidence: 95%
“…A patient with resistant psychosis responded to the treatment with a maximum dose of 80 mg/d of ziprasidone without worsening of motor function (Connemann and Schondeldt-Lecuona, 2004). Another PD patient was treated with 40 mg of ziprasidone and developed elevation of creatinine kinase and body temperature so that neuroleptic malignant syndrome was discussed in this patient and ziprasidone was stopped (Gray, 2004). More data concerning the treatment of psychosis in PD with ziprasidone are lacking.…”
Section: Discussionmentioning
confidence: 95%
“…22 There was also a case report of a patient with PD treated with ziprasidone who developed a neuroleptic malignant syndrome. 23 In our series, patients improved significantly using scales that evaluate mental condition (UPDRS I) and the complications caused by dopaminergic drugs (UPDRS IV). The effect of ziprasidone on psychotic symptoms explains the improvement in mental condition, as seen with item 2 of UPDRS I.…”
Section: Discussionmentioning
confidence: 97%
“…135 One case report also described a patient with PD who developed neuroleptic malignant syndrome when treated with ziprasidone. 136 Based on a case series, Oechsner and Korchounov suggested that an intramuscular injection of ziprasidone (10-20 mg) may successfully treat acute agitation in patients with psychosis in PD, without deterioration of motor function or other clinically relevant side effects. 137 Aripiprazole.…”
Section: Second-generation Antipsychotics (Serotonindopamine Antagonimentioning
confidence: 99%